2005
DOI: 10.1080/00288233.2005.9513678
|View full text |Cite
|
Sign up to set email alerts
|

Associations between β‐casein genotype and milk yield and composition in grazing dairy cows

Abstract: Milk samples from New Zealand dairy cows at pasture were analysed to investigate the relationship between β-casein genotype and milk yield or composition traits. A total of 1661 milk samples from 21 North Island herds were analysed from individual cows in mid lactation, from a routine herd-test taken between mid November 2000 and early February 2001. The cows, whose ages ranged from 2 to 11 years, were the daughters of 11 widely used Holstein-Friesian bulls. The β-casein genotypes of the sires (A 1 or A 2 alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 8 publications
0
9
0
4
Order By: Relevance
“…But according to Ng- Kwai-Hang et al (1984), Bovenhuis et al (1992), Ortner et al (1995) and Cardak (2005), the beta casein genotypes had an effect on milk. Morris et al (2005) showed superiority of A2 genotype with reference to milk yield in Holstein cattle. Tolenkhomba and Yadav (2012) also studied beta casein genotypes in Indian Sahiwal cattle and showed that cows with AB genotype produced more milk (11.81±2.10) than those with AA genotype whose values were 6.48±0.41.…”
Section: Genotype Effectsmentioning
confidence: 93%
“…But according to Ng- Kwai-Hang et al (1984), Bovenhuis et al (1992), Ortner et al (1995) and Cardak (2005), the beta casein genotypes had an effect on milk. Morris et al (2005) showed superiority of A2 genotype with reference to milk yield in Holstein cattle. Tolenkhomba and Yadav (2012) also studied beta casein genotypes in Indian Sahiwal cattle and showed that cows with AB genotype produced more milk (11.81±2.10) than those with AA genotype whose values were 6.48±0.41.…”
Section: Genotype Effectsmentioning
confidence: 93%
“…Ikonen et al (2001) reportaron un incremento en la producción de leche en vacas de primera lactancia con presencia del alelo A2, Morris et al (2005) refieren al genotipo A2A2 como el más favorable para producción lechera y Olenski et al (2012) concluyeron que el alelo A2 es un marcador para mayor producción de leche y proteína.…”
Section: Resultados Y Discusiónunclassified
“…La frecuencia del alelo que codifica la proteína A2 en los animales genotipados es de 0,55 semejante a la estimada en otras poblaciones europeas actuales de Holstein (Massella et al, 2017) y a la estimada hace décadas en las poblaciones de Holstein estadounidenses (van Eenennaam y Medrano, 1991). No obstante, es superior a la estimada en las poblaciones de Holstein canadiense (Ng- Kwai-Hang et al, 1984) y neozelandés (Morris et al, 2005), y en la población española de Holstein-Frisón de la década de los ochenta (Tejedor, 1986), en las que el alelo que codifica la proteína A1 era el más frecuente. Las frecuencias genotípicas estimadas han sido 0,31 para A2A2, 0,48 para A1A2 y 0,21 para A1A1, indicando que la población está en aparente equilibrio de Hardy-Weinberg (p < 0,05) para la β-caseína.…”
Section: Frecuencias Alélicas Y Genotípicasunclassified
“…Estos resultados son coincidentes con las asociaciones referidas en otras poblaciones Holstein; el alelo que codifica la proteína A2 se asocia a un aumento de la cantidad de leche y proteína y un menor contenido de grasa, lo que le llevó a ser considerado como un mar-cador para la selección de cantidad de proteína y leche (Lin et al, 1989;Morris et al, 2005;Olenski et al, 2010). Sin embargo en otros trabajos, el alelo de la proteína A2 por sí sólo no mostraba relación con la producción de leche y proteína, presentando únicamente relación en combinación con el gen de la κ-caseína (Ojala et al, 1996).…”
Section: Frecuencias Alélicas Y Genotípicasunclassified
See 1 more Smart Citation